Spiral breast computed tomography with a photon-counting detector (SBCT): The future of breast imaging?. Issue 157 (December 2022) - Wetzl, Matthias; Dietzel, Matthias; Ohlmeyer, Sabine; Uder, Michael; Wenkel, Evelyn
Abstract: Dedicated breast computed tomography (BCT) is an emerging breast imaging modality. The latest development has been the introduction of a spiral breast computed tomography scanner equipped with a photon-counting detector (SBCT). SBCT promises multiple advantages: Unlike conventional mammography, contrast enhanced spectral mammography (CESM: both 2D), and digital breast tomosynthesis (DBT: pseudo 3D), SBCT enables 3D breast imaging without tissue overlap. SBCT achieves high isotropic spatial resolution of breast tissue enabling the assessment of both soft tissue and microcalcifications. Similar to CESM and MRI, SBCT supports contrast-enhanced imaging, enabling the assessment of breast neovascularization. Unlike mammography and its derived methods (CESM, DBT), SBCT does not require compression of the breast. Accordingly, women consistently report significantly increased patient comfort compared to mammography in a previous investigation. Radiation safety is crucial in breast imaging. Studies showed different results in terms of dose, with some staying within the limits of two-view FFDM defined by the ACR and others exceeding the limit by up to 21%. Therefore, a higher radiation dose compared to state-of-the-art mammography and DBT systems has to be acknowledged. SBCT is currently under scientific investigation in multiple trials. Three major indications are currently explored: Whereas our colleagues in Zurich/Switzerland investigate the role of SBCT for opportunistic screening, in our department SBCT is mainly indicated for the work-up of equivocal lesions, and for preoperative staging. In this narrative review, we summarize the concepts of SBCT and potential implications for patient care. We report on our initial clinical experience with the technology and outline future developments of SBCT.